Integrating Ethnoscience into Eco-Gamified Problem-Based Learning to Improve Sustainability Literacy and Environmental Awareness in Peatlands - Mohamad Nor Aufa; Gusti Nida Nurkhaliza; Muhammad Hasbie; Rusmansyah Rusmansyah (Universitas Lambung Mangkurat, 2026)
This study aims to analyze the effect of implementing the ethnoscience-based Eco-Gamified Problem-Based Learning (PBL) model within peatland contexts on the sustainability literacy and environmental awareness of junior high school students. A quasi-experimental design with a non-equivalent control group was employed, involving 65 students (32 in the experimental group and 33 in the control group). The experimental group received the Eco-Gamified PBL intervention integrating peatland ethnoscience, while the control group received conventional instruction. Data were collected through a sustainability literacy test, an environmental awareness questionnaire, and observation sheets, then analyzed using the N-Gain test and an independent-samples t-test. The results demonstrated that the average sustainability literacy score in the experimental group increased from 56.80% to 84.10%, with an N-Gain of 0.63 (moderate), while the control group improved from 55.30% to 72.40%, with an N-Gain of 0.38 (moderate). Hypothesis testing indicated a significant difference between the two groups (p = 0.003; p < 0.05). Additionally, students’ environmental awareness in the experimental group achieved an average score of 4.28 (very high), significantly higher than the control group’s 3.65 (high), with a significance value of p = 0.002, p < 0.05). These findings demonstrate that integrating peatland ethnoscience into an Eco-Gamified PBL framework effectively enhances students’ sustainability competencies. This study provides empirical evidence for integrating local ecological knowledge and gamification into problem-based learning to support contextualized sustainability education.